Bankruptcy Prediction Models and Stock Prices of the Coal Mining Industry in Indonesia - Ghazali Syamni; M. Shabri Abdul Majid; Widyanana Verawaty Siregar (Faculty of Economic and Business, 2018)
Various bankruptcy prediction models have been used to measure the movement of stock prices, and thus the firms’ performance. This study is aimed at empirically exploring the usefulness of the Olhson, Almant Modification, Grover, Springate, and Zmijewski models for predicting bankruptcy of the 19 coal mining companies. It also attempts to measure the effects of the scores of these bankruptcy prediction models on the stock prices of the coal mining companies in Indonesia. The technique of analysis that used in this research is panel regression. The results of the study showed that the bankruptcy prediction scores of the Ohlson and Almant Modification were found to be the dominant prediction models that affected the stock prices of the coal companies in Indonesia. This indicates that the bankruptcy prediction model can be used as one of the approaches to measure the movement of stock prices and performance of the coal mining companies in Indonesia.DOI: 10.15408/etk.v17i1.6559